The Role of Innovation Attributes in the Successful Implementation of Merdeka Curriculum: A Literature Study - Utami, Nurfika Putri; Susanti, Rahmi; Maharani, Siti Dewi; Anwar, Yenny (Universitas Sang Bumi Ruwa Jurai, 2025)
The Merdeka Curriculum is a national educational innovation in Indonesia that promotes flexibility, contextualization, and student-centered learning. Despite its potential, the implementation of this curriculum faces various challenges, particularly in terms of teacher readiness and their perception of the new policy. This study examines the role of innovation attributes as defined by Everett Rogers’ diffusion of innovation theory in influencing the success of the Merdeka Curriculum’s adoption. The five attributes analyzed include relative advantage, compatibility, complexity, trialability, and observability. Using a literature review approach, this analysis focuses on scholarly articles and research reports on the implementation of the Merdeka Curriculum in Indonesia published between 2023 and 2025. Findings indicate that relative advantage and compatibility positively contribute to curriculum acceptance, while complexity remains a major obstacle at the practical level. Meanwhile, trialability and observability accelerate adoption at the school level by providing visible and evaluable outcomes. These results have practical implications for policymakers and educational institutions to design more effective implementation strategies, including teacher training and context-based adaptation approaches. By situating the Merdeka Curriculum within the framework of innovation diffusion, this article contributes to a deeper understanding of how policy adoption in education can be better adopted through alignment with innovation attributes.